Adjustment cost-driven inflation inertia - Sebastian Sienknecht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper shows how endogeneous inflation inertia is generated by a simple modificaton of the quadratic adjustment cost structure faced by economic agents. We derive the pertinent inflation relationships based on purely nominal rigidities and show that they always involve additional expectation terms which are absent in a Calvo-type environment. However, the structural differences do not prevent dynamic adjustment paths and theoretical moments to be similar under both rigidity assumptions. An extensive application of nominal adjustment frictions leads to a full-scale macroeconomic framework able to replicate empirical responses to an interest rate shock.
Keywords: E31; E32; E52; 330; Inflation Dynamics; New Keynesian Phillips Curve; Business Fluctuations; Inflation; Hysteresis; Preisrigidität; Anpassungskosten; New-Keynesian Phillips Curve; Konjunktur; Theorie